Fullerene and fullerene-aluminum nanostructured films as sensitive layers for gas sensors - Grynko, D.; Burlachenko, J.; Kukla, O.; Kruglenko, I.; Belyaev, O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The responses of quartz crystal microbalance (QCM) sensors coated by fullerene and fullerene-aluminum films to ethanol and water vapors are investigated. The possibility of controlling the adsorption properties of such films by inserting the aluminum and by ultraviolet irradiation that changes the film morphology in a definite way is demonstrated.